A Universal Digital Stress Management Intervention for Employees: Randomized Controlled Trial with Health-Economic Evaluation - Freund, Johanna; Smit, Filip; Lehr, Dirk; Zarski, Anna-Carlotta; Berking, Matthias; Riper, Heleen; Funk, Burkhardt; Ebert, David Daniel; Buntrock, Claudia (Journal of Medical Internet Research, 2024)
BACKGROUND: Stress is highly prevalent and known to be a risk factor for a wide range of physical and mental disorders. The effectiveness of digital stress management interventions has been confirmed; however, research on its economic merits is still limited. OBJECTIVE: This study aims to assess the cost-effectiveness, cost-utility, and cost-benefit of a universal digital stress management intervention for employees compared with a waitlist control condition within a time horizon of 6 months. METHODS: Recruitment was directed at the German working population. A sample of 396 employees was randomly assigned to the intervention group (n=198) or the waitlist control condition (WLC) group (n=198). The digital stress management intervention included 7 sessions plus 1 booster session, which was offered without therapeutic guidance. Health service use, patient and family expenditures, and productivity losses were self-assessed and used for costing from a societal and an employer's perspective. Costs were related to symptom-free status (PSS-10 [Perceived Stress Scale] score 2 SDs below the study population baseline mean) and quality-adjusted life years (QALYs) gained. The sampling error was handled using nonparametric bootstrapping. RESULTS: From a societal perspective, the digital intervention was likely to be dominant compared with WLC, with a 56% probability of being cost-effective at a willingness-to-pay (WTP) of €0 per symptom-free person gained. At the same WTP threshold, the digital intervention had a probability of 55% being cost-effective per QALY gained relative to the WLC. This probability increased to 80% at a societal WTP of €20,000 per QALY gained. Taking the employer's perspective, the digital intervention showed a probability of a positive return on investment of 78%. CONCLUSIONS: Digital preventive stress management for employees appears to be cost-effective societally and provides a favorable return on investment for employers. TRIAL REGISTRATION: German Clinical Trials Register DRKS00005699; https://drks.de/search/en/trial/DRKS00005699.
CRIS-Team Scopus Importer:2024-11-01
Keywords: cost-benefit; cost-effectiveness; cost-utility; economic evaluation; employees; internet-based; return-on-investment; stress management; universal prevention